Silver Stained Nucleolar Organizing regions [AgNOR] in Metastatic Carcinoma to peritoneal cavity - Mazin J. Al-Baldawy (مجلة كلية الطب, 2009)
Background : AgNOR parameters are well known to pathologists as a proliferation marker with advantage over other proliferation markers of being cheaper, simpler and able to assess proliferation speed as well as state , AgNOR stainability was found to be well preserved in smears kept for up to 2 years , studies have shown that AgNOR values can serve as a useful prognostic parameter and a marker for tumour progression in different carcinomas (1) This study was conducted to see the importance of AgNOR staining in the peritoneal fluid cytopathological examination Patient and Methods: It was a descriptive and prospective study conducted in Department of cytopathology in the medical city and Department of pathology n the medical college of Baghdad University, from September 2003 to June 2007. AgNOR staining was performed on 50 peritoneal fluid specimens having malignant cells and 20 other peritoneal fluid specimens as control cases Results: AgNOR count, size and dispersion were normal in benign mesothelial cells (the proportion of cells with 1 or 2 AgNOR dots ranged from 32% to 98% with a median of 82% and a mean of 80.7%, S.D. 15.4 the proportion of cells with clusters ranged from 0% to12% with a median of 0% and a mean of 1.3%, S.D. 2.5 ) , higher in the malignant cells(the proportion of cells with 1 or 2 AgNOR dots ranged from 15% to 75% with a median of 30.5% and a mean of 28.9%, S.D. 21.1, the proportion of cells with clusters ranged from 23% to88% with a median of 67.6% and a mean of 56.2%, S.D. 36.7 ). AgNOR counts in the malignant cells were significantly greater as compared with counts of normal mesothelial cells . Conclusion: Typing of AgNOR count, size and dispersion was found to be an important marker in differentiation between normal mesothelial cells and malignant cells of metastatic adenocarcinoma